Synthesis of cobalt hexacyanoferrate nanoparticles and its hydrogen storage properties. (19th April 2018) - Kumar, Asheesh; Kanagare, A.B.; Banerjee, S.; Kumar, Pradip; Kumar, M.; Jagannath,; Sudarsan, V.
Abstract: In the present paper, we report hydrogen storage properties of cobalt hexacyanoferrate nanoparticles as a function of temperature. Cobalt hexacyanoferrate nanoparticles were synthesized by facile chemical precipitation method. The resulted compound forms FCC structure analogous to Prussian blue and is found to be stable up to 550 K. Presence of characteristic absorption bands in the range of 2000–2300 cm −1 in IR spectra corresponds to the CN stretching frequency of Fe(III)CNCo(II) sequence and this confirms the formation of Prussian blue analogues. Hydrogen adsorption studies were performed at variable temperatures. The effect of precursor concentration on hydrogen storage property has been investigated and interestingly, with increase in cobalt precursor concentration, hydrogen storage capacity is found to decrease. This correlates well with openness of the crystal structure. To the best of our knowledge, this is the first report on hydrogen storage properties of cobalt hexacyanoferrate. Graphical abstract: Highlights: Cobalt hexacyanoferrate is prepared by simple solution route. Hydrogen adsorption property is reported for the first time. Cage structure is responsible for hydrogen storage.